Impact of the Foreign Banks Entry on the Accounting Profits of the Jordanian Commercial Banks (1995–2015) - Al-Neimat, Mahmoud Atallah; Warred, Talib Mohammad Musa (International Journal of Economics and Financial Issues, 2017)
The objective of this study is to analyze the impact of foreign banks entry on the accounting Profits of the Jordanian commercial banks. Study sample included (18) banks and covering the period (1995-2015).The data was obtained from the bank's annual financial reports. The study used an econometric model to measure the relationship between the economic variables; accounting profit, size, foreign entry, equity level, operating expenses and capital scarcity. Before the estimation process, the required econometrics tests were implemented to compare between the different models, including: panel least squares, fixed-effect model, random- effect model and Hausman test. The study finding presence redacted to appositive and statistically significance of the operational expenses on the accounting profit, and to presence is positive and significant impact of the foreign banks entry on the accounting profits of the Jordanian commercial banks, this effects came through developing the banking work and increasing the competition degree, and attracting technology, which contributed to motivate the Jordanian commercial banks and pushing them to develop their works and services to become compatible with the advanced foreign banks. Keywords commercial banks; foreign banks; accounting profi JEL Classifications: G21, M41